Blackcurrant (Ribes nigrum L.) and Kamchatka Honeysuckle (Lonicera caerulea var. Kamtschatica) Extract Effects on Technological Properties, Sensory Quality, and Lipid Oxidation of Raw-Cooked Meat Product (Frankfurters) - Lukáš Jurčaga; Marek Bobko; Adriana Kolesárová; Alica Bobková; Alžbeta Demianová; Peter Haščík; Ľubomír Belej; Andrea Mendelová; Ondřej Bučko; Miroslav Kročko; Matej Čech (Foods, 2021)
Oxidation is one of the most prevalent factors responsible for meat product deterioration. Due to their potential health risks, commonly used synthetic antioxidants are beginning to be frowned upon by customers. The industry is searching for a natural replacement. In our study, we incorporated blackcurrant (Ribes nigrum L.) and Kamchatka honeysuckle (Lonicera caerulea var. Kamtschatica) extracts into raw-cooked meat products (frankfurters) as natural antioxidants. We observed that both extracts at concentrations of 3 mL·kg−1 were able to significantly (α = 0.05) postpone lipid oxidation in our samples, with results comparable to vitamin C (0.5 mg·kg−1) addition. Moreover, we did not observe negative effects of the extracts on the product’s color, pH, or textural properties. Negative results were reported in the sensory evaluation of honeysuckle addition samples. This could have been caused by the natural strong and bitter taste of honeysuckle, which was transferred to the extracts and, subsequently, into the meat product.